BLOK AMBALAT ANTARA SENGKETA DAN PELUANG KERJA SAMA EKONOMI - nuruzzaman, farhan (FEB Universitas Sam Ratulangi Manado, 2025)
So far, descriptions of the Ambalat block have focused more on the maritime border dispute between Indonesia and Malaysia. This border dispute has been ongoing since the old order to the reform era. Even since 2005 to 2022, negotiations have stalled and are in a status quo position. This article attempts to review the dispute and the possibility of building economic and trade cooperation through the concept of joint development. Discussion of Joint Development does not mean ignoring border disputes but rather seeking a new formulation that better meets the needs of the people in the countries in dispute. In addition to the Joint Development concept, the concept of international cooperation and the concept of developing border areas are also used. The description uses a descriptive analysis approach that attempts to describe the tendencies of the development of political phenomena in both Indonesia and Malaysia as well as a description of Joint Development and international cooperation carried out by Indonesia and Malaysia, including cross-border maritime agreements. Keyword: Ambalat block, disputes and Joint Development